The adoption of innovation in ruminant farming for food security in Malaysia: a narrative literature review - Abdullah, Farah Adila; Ali, Jamal; Noor, Mohd Saifoul Zamzuri (2020)
The ruminant sub-sector is vital in the agriculture sector as one of the protein sources besides poultry and fish. In recent years, the self sufficiency level (SSL) of ruminant meat in Malaysia is discouraging, while the import value kept increasing. Yet, food security has become a crucial issue in meat production. However, it believed that adopting innovation in ruminant farming can improve production if it used in the right way. Nevertheless, there is still a lack of understanding on this matter. Hence, this paper aims to review the existing literature to elaborate on the current situation in ruminant farming and factors influencing farmers toward the adoption of innovation.This review would be beneficial for researchers and stakeholders to improve the existing policy and enhancing ruminant meat production through innovation.